PIEZO1 activity promotes stemness in mesenchymal stem cells under shear stress and enhances protection of leukemia cells - Amit Sharma; Jina Bhattacharyya; Piruthivi Sukumar; Bithiah Grace Jaganathan (Scientific Reports)
Abstract Mesenchymal stem cells (MSCs) differentiate into cells of multiple lineages and play an essential role in bone formation, tissue regeneration, immunomodulation and are also necessary to maintain hematopoiesis in bone marrow. The lineage commitment of MSCs into osteoblasts is controlled by several factors including mechanical signals from the microenvironment. Mechanosensor proteins regulate the interaction of the cells with the microenvironment and control several cellular functions. Here, we determined the cellular effects of PIEZO1, a mechanically activated ion channel protein on proliferation, differentiation, migration, and leukemia support of human bone marrow-derived MSCs (BM-MSCs). Activation of PIEZO1 negatively impacted the proliferation, osteogenic differentiation, and migration ability of BM-MSCs and PIEZO1 downregulation reduced the self-renewal and differentiation ability, but partially reversed the inhibitory effects of PIEZO1 activation (through yoda1) on differentiation and migration. PIEZO1 activity modulates the shear-stress response in BM-MSCs, resulting in downregulation of PIEZO1 expression. Concurrently, this reduction activates Notch signaling pathway and upregulates genes associated with stemness. In addition, PIEZO1 activity mediates the chemoprotective ability of BM-MSCs on leukemia cells by modulating the interaction between the MSCs and leukemia cells. Our findings suggest that a calibrated PIEZO1 activity is required in BM-MSCs to maintain their differentiation, proliferation and migration ability and PIEZO1 regulates the interaction of BM-MSCs with the hematopoietic cells.